Patient and surgical factors affecting procedure duration and revision risk due to deep infection in primary total knee arthroplasty - Badawy, Mona (BMC Musculoskelet Disord, 2017)
BACKGROUND: The aim of this study was to assess which patient and procedure factors affected both the risk of infection as well as procedure duration. Additionally, to assess if procedure duration affected the revision risk due to deep infection in total knee arthroplasty (TKA) patients and in a subgroup of low-risk patients. METHODS: 28,262 primary TKA with 311 revisions due to deep infection were included from the Norwegian Arthroplasty Register (NAR) and analysed from primary surgery from 2005 until 31st December 2015 with a 1 and 4 year follow up. The risk of revision due to deep infection was calculated in a multivariable Cox regression model including patient and procedure related risk factors, assessing Hazard Ratio (HR) with 95% confidence interval (CI). RESULTS: Multivariate analysis showed statistically significant associations with revision due to deep infection and increased procedure duration for male patients, ASA3+ (American Society of Anesthesiologists) and perioperative complications. Procedure duration ≥110 min (75 percentile) had a higher risk of deep infection compared to duration <75 min (25 percentile), in the unadjusted analysis (HR = 1.8, 95% CI 1.3-2.5, p = 0.001) and in the adjusted analysis (HR = 1.5, 95% CI 1.0-2.1, p = 0.03). For low-risk patients, procedure duration did not increase the risk of infection. CONCLUSION: Male patients, ASA 3+ patients and perioperative complications were risk factors both for longer procedure duration and for deep infection revisions. Patients with a high degree of comorbidity, defined as ASA3+, are at risk of infection with longer procedure durations. The occurrence of perioperative complications potentially leading to a more complex and lengthy procedure was associated with a higher risk of infection. Long procedure duration in itself seems to have minor impact on infection since we found no association in the low-risk patient.